(untitled) (Research, Society and Development, 2022)
Objective: To present, based on the scientific literature, the diagnosis of HELLP Syndrome in Primary Care and how nursing is inserted in this context. Methodology: This is an integrative literature review, carried out in the Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SCIELO), Nursing Database (BDENF) and Google Scholar, articles published between 2018 and 2022 and written in Portuguese were used. Results: A total of 1,036 articles were found, after applying the inclusion and exclusion criteria, 11 articles were selected, 1 articles in LILACS, 0 in SCIELO, 2 in BDENF and 8 in Google Scholar, after careful selection of the results of the information was made in a descriptive way and predisposed the stage of data extraction: author / year of publication, title / database and general objective. Conclusion: Therefore, in accordance with the findings in the literature, HELLP Syndrome represents a serious problem in pregnancy, mainly because it is associated with pre-eclampsia and eclampsia, which together are complications that pose a risk to mother and baby. Where it is perceived that the primary care nurse has great responsibility in the diagnosis of this syndrome, being essential to have knowledge of it and know how to act.